A Practice Theory of Legal Pluralism: Hart's (inadvertent) defence of the indistinctiveness of law. Issue 1 (January 2014) - Croce, Mariano
Abstract : This article claims that H.L.A. Hart's theory may be regarded as a sound vindication of what today is known as legal pluralism. In short, Hart's practice theory of norms attests to the fact that state law is only one system of rules among many others, and that it does not exhibit any distinctive feature that may distinguish it from those others. I will depict this as an inadvertent but extremely valuable outcome of the practice theory. Indeed, Hart's battle against the claimed connection between law and coercion and his firm conviction that legal normativity should be understood in light of the broader phenomenon of social normativity make his practice theory of rules a sound and fertile vindication of legal pluralism as a theoretical approach to legal phenomena. As a result, even though Hart was a legal centralist and a legal monist, his theorizing ends up dismantling the identity between the general phenomenon of law and the law of the state . I will proceed as follows: I will first look at the contentious issue of the relation between law and coercion by examining how two prominent legal scholars, Hans Kelsen and E. Adamson Hoebel, came to the conclusion that the distinguishing mark of law is coercion (sec. 1). This analysis will be instrumental in demonstrating that Hart failed to grasp the relevance and salience of the relation between law and coercion, and in particular, the peculiar role Kelsen and Hoebel attributed to the latter (sec. 2). I will argue that Hart's discomfort with the emphasis on the notion of coercion was due not to the nature of this notion as such, but to the distortive effect its overemphasis had exerted on positivist legal theorizing. I will claim that Hart's most insidious adversaries were two (at the time prominent) philosophical and jurisprudential streams, namely, behaviourism and emotivism (sec. 3). I will go on to say that Hart's arguments against these adversaries are well addressed but inadequate, and will try to reinforce them by drawing on a Wittgensteinian view of practices (sec. 4). I will conclude by showing that the consistent outcome of a "reinforced" practice theory is a highly pluralist view of law (sec. 5).